Pengaruh Profitabilitas pada Agresivitas Pajak dengan Pengungkapan CSR Sebagai Variabel Moderasi - Shintya Devi, Dewa Ayu Nyoman; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
This study aims to obtain empirical evidence of the effect of profitability on tax aggressiveness. This study also provides empirical evidence of the ability to disclose Corporate Social Responsibility (CSR) to moderate the influence of profitability on tax aggressiveness. Research conducted on companies published on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. The sample is determined through non probability sampling method with purposive sampling technique. The number of samples used in this study were 56 observation samples. The data analysis technique used is the analysis of Moderated Regression Analysis (MRA). The results of this study indicate that profits show a positive effect on tax aggressiveness. The results show CSR disclosure does not moderate the effect of profitability on tax aggressiveness. Agency Theory and Positive Accounting Theory in explaining tax aggressiveness. Keywords: Tax aggressiveness, profitability, corporate social responsibility.